Download presentation
Presentation is loading. Please wait.
2
Linear vs. exponential growth
3
Linear vs. exponential growth: t = 0 A = 1x(1+1) 0 = 1 A = 1x0 + 1 = 1
4
Linear vs. exponential growth: t = 1 A = 1x(1+1) 1 = 2 A = 1x1 + 1 = 2
5
Linear vs. exponential growth: t = 2 A = 1x(1+1) 2 = 4 A = 1x2 + 1 = 3
6
Linear vs. exponential growth: t = 3 A = 1x(1+1) 3 = 8 A = 1x3 + 1 = 4
7
Linear vs. exponential growth: t = 4 A = 1x(1+1) 4 = 16 A = 1x4 + 1 = 5
8
Linear vs. exponential growth: t = 5 A = 1x(1+1) 5 = 32 A = 1x5 + 1 = 6
9
Linear vs. exponential growth: t = 6 A = 1x(1+1) 6 = 64 A = 1x6 + 1 = 7
10
fin
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.